2011
DOI: 10.25182/jgp.2011.6.3.178-185
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Status Besi Dan Kebugaran Fisik Pekerja Wanita Usia Subur

Abstract: The study aims were to (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
2
0
3
Order By: Relevance
“…Various studies conducted in Indonesia have proven that consumption of iron (Fe) with vitamin C has an effect on increasing haemoglobin levels. Similar results were found in Indriani's study (2013), which showed an increase in Hb levels after iron and vitamin C supplementation with an average increase of 2.7 g/dL [13] . These results are also supported by Tuti's study (2013), which found that giving iron tablets twice a week or once a week to pregnant women showed a better increase in Hb levels if accompanied by the addition of vitamin C [14].…”
Section: Nutritional Content Test Results Of Modi Ed Biscuitssupporting
confidence: 89%
See 1 more Smart Citation
“…Various studies conducted in Indonesia have proven that consumption of iron (Fe) with vitamin C has an effect on increasing haemoglobin levels. Similar results were found in Indriani's study (2013), which showed an increase in Hb levels after iron and vitamin C supplementation with an average increase of 2.7 g/dL [13] . These results are also supported by Tuti's study (2013), which found that giving iron tablets twice a week or once a week to pregnant women showed a better increase in Hb levels if accompanied by the addition of vitamin C [14].…”
Section: Nutritional Content Test Results Of Modi Ed Biscuitssupporting
confidence: 89%
“…Vitamin A de ciency also worsens iron de ciency anaemia (IDA) status [15]. Several studies have shown that there is an interaction between vitamin A and iron, which is marked by a decrease in the prevalence of anaemia [13], [16], [17]. In addition, if a pregnant woman has a long-standing micronutrient de ciency, there is a risk that the child will be born with stunting.…”
Section: Nutritional Content Test Results Of Modi Ed Biscuitsmentioning
confidence: 99%
“…Penelitian ini sejalan dengan penelitian Yulianingsih (2013), dimana konsumsi protein rata-rata pada wanita bekerja dan wanita usia subur yaitu 84,2 gram, rata-rata kadar hemoglobin 12,3 g/dl dengan kadar hb minimum yaitu 10,5 g/dl dan mayoritas wanita bekerja memiliki kadar Hb normal yaitu ≥ 12 g/dl, hanya 34,6% wanita bekerja dengan kadar Hb < 12 g/dl. Selain itu didukung oleh penelitian (Indriani et al, 2011), yang menunjukkan bahwa sebanyak 50% responden memiliki tingkat hemoglobin rendah dengan status anemia, juga secara statistik menunjukkan bahwa terdapat hubungan yang signifikan antara asupan protein dengan kejadian anemia.…”
Section: Pembahasan Pengaruh Asupan Protein Terhadap Kadar Hemoglobinunclassified
“…Suatu studi yang dilakukan di Tangerang, bahwa prevalensi anemia pada pekerja wanita mencapai 69% (Suyardi et al, 2016). Pekerja yang menderita anemia berdampak terhadap produktivitasnya yaitu 20% lebih rendah dibandingkan pekerja dengan kondisi yang sehat (Indriani et al, 2011). Menurut (Kusriyana et al, 2010), wanita yang mengalami kekurangan energi dan protein menyebabkan pekerja menjadi lambat berpikir untuk bertindak serta cepat lelah, sebaliknya ditemukan pengaruh signifikan dengan meningkatnya kadar Hemoglobin pekerja wanita dapat meningkatkan produktivitas kerja.…”
unclassified
“…19 Hasil penelitian ini juga sejalan dengan yang dilakukan oleh Indriani yang melakukan penelitian tentang peningkatan status besi dan kebugaran fisik pekerja wanita usia subur dan menyimpulkan pemberian suplemen zat besi 3 kali sehari selama 10 minggu mampu meningkatkan kadar feritin dan kebugaran fisik pekerja wanita usia subur. 20…”
Section: Pendahuluanunclassified